PENGARUH KECEPATAN POTONG TERHADAP PERUBAHAN TEMPERATUR PAHAT DAN KEAUSAN PAHAT BUBUT PADA PROSES PEMBUBUTAN BAJA KARBON SEDANG - Sastal, Angga Zeptiawan; Gunawan, Yuspian; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
This research aims to know the influence of the speed rotation spindle against wear and tear andtemperature change the chisel on the process medium carbon steel lathing. This research isexperimental method research by conducting medium carbon steel lathe by using chisel of HighSpeed Steel (HSS) lathe. Rotation speed of 1500 rpm lathe spindle, 1050 rpm and 750 rpm with adepth of cut of 0,5 mm and a 0,5 mm/min feed speed shall be performed every 1 times thepulverizing prises with a slashed workpiece length of 50 mm. Every spindle rotation speed is done3 times the lathe process. Lathe wear and chisel lathe are measured every 1 time of the latheexperiment. The test results in this research show that the speed of rotation of the spindle lathes towear and temperature at 1500 rpm spindle round earned the highest wear 0,463 mm at round 750rpm value acquired spindle lowest wear 0,150 mm, while at 1500 rpm spindle rotation obtained thehighest temperature value of 126,3oC and at 750 rpm spindle spin obtained lowest temperature65,0oC.Keywords: Spindle rotation, steel, HSS, wear and temperature.